2015
DOI: 10.1097/mca.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Low 25-OH vitamin D levels are not associated with coronary artery calcium or obstructive stenoses

Abstract: Low 25-OH vitamin D levels were not associated with CAC or severely obstructive stenoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
(23 reference statements)
0
12
3
Order By: Relevance
“…Our study demonstrated that there is indeed a relationship between serum vitamin D levels and severity of CAD. These results are contrary to those of Ho et al;28 however, this disparity could be attributed to differences in geographic location and ethnicity, as well as a lower CAD prevalence in that study and the absence of female participants. Furthermore, the relatively small sample in the present study was also a contributing factor.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study demonstrated that there is indeed a relationship between serum vitamin D levels and severity of CAD. These results are contrary to those of Ho et al;28 however, this disparity could be attributed to differences in geographic location and ethnicity, as well as a lower CAD prevalence in that study and the absence of female participants. Furthermore, the relatively small sample in the present study was also a contributing factor.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation was made in dialysis patients where a U-shape curve has been noticed, where low serum vitamin D levels, as well as high levels, are associated with vascular calcification [13,50,51]. However, other authors have postulated that there is insufficient evidence to support a consistent association between low vitamin D levels and coronary artery calcium (CAC) [55], or that there is definitely no association between low 25(OH)D and CAC, or severely obstructive coronary artery stenosis [56]. Nevertheless, single nucleotide polymorphisms (SNPs) in the CYP24A1 gene, associated with vitamin D metabolism, have been independently linked with coronary artery calcification [57].…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D receptors can be found in most tissues including heart muscle. It has some important roles in maintaining normal function of muscles and controlling the inflammatory process and immune system [21]. Another explanation of the relation of vitamin D deficiency and CAD can be the vitamin D deficiency associated abnormalities such as metabolic syndrome, obesity, insulin resistance, diabetes, hypertension and hyperlipidemia, which all have significant relationship with cardiovascular abnormalities [6,20,22,23].…”
Section: Discussionmentioning
confidence: 99%